THE EFFECTIVENESS OF THINK PAIR SHARE MODEL WITH SCIENCE LITERACY APPROACH IN IMPROVING STUDENTS' ARGUMENTATION ABILITY - Susilo, Aji; Sofwan Hadi (Science Education, Institut Agama Islam Negeri Ponorogo, 2025)
Argumentation ability is an important skill in learning. However, in classroom learning, there are still many students who have difficulty in constructing strong arguments. One strategy that can be applied to improve students' argumentation skills is the Think Pair Share type cooperative learning model with a science literacy approach. This model encourages students to think independently, discuss with peers, and share understanding with the group, so that they are more active in building concepts and presenting scientific arguments. The type of research used was quantitative with a quasi-experimental design. The population in this study were VIII grade students at MTs Darul Huda Mayak Ponorogo with research samples in class VIII.2 with 30 students and class VIII.3 with 30 students. The data collection technique was carried out by pretest and posttest of students' argumentation skills. The results showed that the implementation of learning got a percentage of 92.30%, including in the very good category. The average posttest score of the experimental class was 76.80, while the control class was 58.27. The results of the independent sample t-test also showed a significant difference in students' argumentation skills between the experimental and control classes. While the N-Gain test shows a result of 58.8556 which is included in the moderately effective category. These findings indicate that the Think Pair Share type cooperative learning model with a science literacy approach can be a strategy that can improve students' scientific argumentation skills in learning science actively and meaningfully.